How Can a Process of Reflection Enhance Teacher-Trainees' Practicum Experience? - Diana Zulimay Camacho Rico; Lucy Durán Becerra; Judith C. Albarracin Trujillo; Marjorie Verónica Arciniegas Vera; Magdaleydy Martínez Cáceres; Gabriel Eduardo Cote Parra (Asociación Colombiana de Profesores de Ingles, 2012)
The present study was an attempt to understand how a process of reflection helped five foreign language student teachers throughout their first teaching experience. This study was conducted in the classrooms of five public schools in Colombia where English was taught to high school students. Data were collected through classroom observations, students' reflective journals, lesson plans and semi-structured interviews. Findings revealed that reflection is a way to help foreign language student teachers to improve their first teaching practice. The analysis was based on the light of two theories, reflection in action and reflection on action from Schön (1987) and Van Manen's (1977) three levels of reflection.